KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN PRESTASI AKADEMIK PESERTA DIDIK: STUDI KASUS DI MTSN 3 JOMBANG - liila Fiqi Ailisia; H. Moh. Syamsul Falah (Jurnal Manajemen Pendidikan, 2026)
Madrasah principal leadership is a key determinant of Islamic educational institution success. Weak and ineffective leadership often causes low student achievement and suboptimal institutional management. This study aims to analyze: (1) the principal’s leadership style and approach, (2) students’ academic achievement, and (3) the role of principal leadership in improving academic achievement at MTsN 3 Jombang. A qualitative descriptive case study approach was employed. Data were collected through comprehensive observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. Data validity was ensured through source, technique, and time-based triangulation, confirmed by member checks. Findings reveal: (1) leadership is implemented through five integrated roles educator, manager, administrator, supervisor, and innovator/motivator with a visionary communicative-participatory style; (2) students’ academic achievement develops sustainably through a structured system encompassing multidimensional measurement, talent identification, individualized coaching, and responsive policies; (3) principal leadership significantly contributes to improving student achievement from district to national level through the Takhassus Center program, robotics coaching, Islamic science olympiads, and a cross generational institutionalized achievement culture.